Simulation and Test Study of Blast Crater in Deep Ore Body of Metal Mine Based on Lsdyna - Erhu Dong; Long An; Yuanhui Li; Jiahua Zhang (Shock and Vibration)
The blast technology in metal mining is still the most important method of ore body mining. With the increase of mining depth, the blast process is more and more affected by the rock mechanical properties of the ore body, explosive properties, and crustal stress. In order to study the effects of rock physical and mechanical properties of the ore body, explosive detonation pressure and deep crustal stress on powder factor, blast action index and blast vibration. In this paper, a numerical simulation method under the fluid-solid coupling algorithm of rock body and explosive is constructed by combining the on-site blast crater test, Lsdyna JHC (Johnson Holmquist Concrete) damage model, and MATLAB parameter fitting algorithm. First, an exponential fitting function of the type “y=A×ex/B+C” is proposed to measure the rock body structure. Second, by modulating the strength and damage parameters and defining the unit failure criterion, the damage volume and blast action index obtained from the dynamic calculation are consistent with the 3D scanning results of the on-site blast crater test. Finally, the difference in HHT (Hilbert–Huang Transform) analysis results between the vibration signals of the surrounding rock body in simulation and test is clarified. By combining the blast crater test of the ore body and the numerical simulation of Lsdyna, the prediction of powder factor, blast action index, and blast vibration intensity is realized, which provides a reference for the controlled blasting of the deep ore body.